Downstream strategies of liquid smoke products as a preservative and smoke aroma in fishery products: Strategi hilirisasi produk asap cair sebagai pengawet dan aroma asap pada produk perikanan - Budiati, Lilin; Swastawati, Fronthea; Syakur, Abdul; Suharto, Slamet; Hasthi, Saputra; Anggo, Apri Dwi (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2024)
Smoked fish is a fishery product that meets the nutritional needs of the population. The traditional smoking method leads to the production of H2S, which reduces the aroma and is carcinogenic. The liquid smoke technology offers a solution to the challenges associated with the application of traditional smoking methods. However, the use of the liquid smoke method remains limited in smoked fish businesses. This study aimed to evaluate and develop a downstream strategy for producing and distributing liquid smoke to facilitate its implementation by smoked fish businesses based on SWOT analysis. This study employed a quantitative descriptive methodology utilizing the strengths, weaknesses, opportunities, and threats (SWOT) analytical framework. The data were collected through interviews and questionnaires. The obtained data were subjected to weight calculations using the Expert Choice tool. The research findings indicate that the optimal approach for developing downstream liquid smoke products is to create a novel product in the form of liquid smoked fish. Liquid-smoked fish are immersed in or coated with liquid smoke to achieve an extended shelf life and smoky aroma, without traditional smoking methods. In addition, it establishes a strategic alliance between scholars, entrepreneurs, and the government. Strategic relationships can be established by developing a shared agenda focusing on fostering a sustainable blue economy. The blue economy refers to the use of hygienic, healthy, and non-carcinogenic fishing products such as smoked fish to promote sustainable economic growth and enhance community welfare.